Profile of Junior High School Students' Critical Thinking Skills in Answering Questions Related to Biological Concepts - Ahmad Fauzi (Scientiae Educatia: Jurnal Pendidikan Sains)
There are indication that the implementation of education in various places in Indonesia is still not optimally empowering students' critical thinking skills (CTS). The aimed of this quantitative study was about 1) to survey the CTS of junior high school students in the Malang, and 2) to know whether or not there were differences in CTS between students in different grades. The measurement of CTS in this study used an integrated critical thinking assessment of the essay test. Mean score and one-way ANOVA were used as data analysis techniques. The results concluded that 1) students’ CTS in Malang were still low; and 2) there was no significant difference in the level of CTS between students of class VII, VIII, and IX.